1992
DOI: 10.1002/nme.1620340120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of softening in elastic‐plastic structural dynamics

Abstract: SUMMARYSoftening, understood as unstable behaviour of material or structural components, is considered herein for its possible consequences on the overall behaviour of discrete dynamic models of elastic-plastic beam structures, in the absence of geometric effects. It is shown that multiplicity of incremental solutions (response bifurcations) and manifestations of overall instability may occur. The bifurcated responses may exhibit different scenarios for the same excitation: e.g. shakedown or local damage up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Ba zant et al (1987a,b) and Maier and Perego (1992), particularly with regard to the deduction of efficient numerical procedures (Ba zant and Mazars, 1990). In the context of concrete frame-like structures, two approaches have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Ba zant et al (1987a,b) and Maier and Perego (1992), particularly with regard to the deduction of efficient numerical procedures (Ba zant and Mazars, 1990). In the context of concrete frame-like structures, two approaches have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical investigations from the viewpoint of applied mechanics have also been conducted (Herrmann, 1965;Ishida and Morisako, 1985;Maier and Perego, 1992;Araki and Hjelmstad, 2000;Williamson and Hjelmstad, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For SDOF systems, it is well known that, if the tangent stiffness becomes negative in a dynamic process, residual displacements increase. For MDOF systems, it has been shown that a negative eigenvalue of the tangent stiffness matrix leads to either the accumulation of deformation in a particular mode (Uetani and Tagawa, 1998) or the localization of deformation (Maier and Perego, 1992). Bernal (1998) indicated that a negative eigenvalue is a necessary condition of dynamic collapse.…”
Section: Introductionmentioning
confidence: 99%
“…This holds also in the present treatment, because the discretized pipeline-soil system involves a number of linearly elastic beam-elements (for the pipeline) with convex energy density and a number of soil-elements with nonconvex energy density [18]. Thus the existence of a solution in each time-step can be assured [12,21,22].…”
Section: H(t) = D(t) * Z(t) + D(t)mentioning
confidence: 99%